2016
DOI: 10.1080/02656736.2016.1191680
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ultrasound-guided high intensity focused ultrasound for the treatment of uterine fibroids in patients with an anteverted uterus and a retroverted uterus

Abstract: The results of this study indicated that uterine fibroids with hypointensity on T2WI in a retroverted uterus can be safely and effectively treated with USgHIFU. However, the fibroids in an anteverted uterus are easier to treat with USgHIFU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…However, the power of 200 W and the sonication duration of 20 s that we employed were much lower than the power of 305-402 W [46][47][48] and sonication duration of 90-3864 s [46][47][48] used in these studies, implying that the immediate effect on the tissue could be different. Furthermore, the ablative target of normal uterus here is generally more vascularized than uterus fibroid targets of these studies [47]. This implies that hemorrhage and/or fluid-filled cavities are a more likely outcome in for our ablation targets compared to uterine fibroids.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, the power of 200 W and the sonication duration of 20 s that we employed were much lower than the power of 305-402 W [46][47][48] and sonication duration of 90-3864 s [46][47][48] used in these studies, implying that the immediate effect on the tissue could be different. Furthermore, the ablative target of normal uterus here is generally more vascularized than uterus fibroid targets of these studies [47]. This implies that hemorrhage and/or fluid-filled cavities are a more likely outcome in for our ablation targets compared to uterine fibroids.…”
Section: Discussionmentioning
confidence: 74%
“…The hyper-intensive lesion shown in the contrast-enhanced MR were consistent with results from a prior publication [45], and matched the severe hemorrhage and fluid-filled cavities observed in the macroscopic and histological results. With that said, some studies found post-ablation targets to be seen as non-perfused areas in the MR images, as opposed to the hyper-intense regions seen here [46][47][48]. However, the power of 200 W and the sonication duration of 20 s that we employed were much lower than the power of 305-402 W [46][47][48] and sonication duration of 90-3864 s [46][47][48] used in these studies, implying that the immediate effect on the tissue could be different.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Compared to the myometrium and skeletal muscle, the signal intensity (SI) on T2WI was classified into hypointense when the SI was similar to that of the normal skeletal muscle, isointense when higher than that of the skeletal muscle but lower than that of myometrium, hyperintense when similar to or higher than that of myometrium, and mixed SI when more than two SI types existed [9]. The location of UFs was divided into anterior, lateral, posterior and fundus, the type of UFs into intramural, subserosa, submucosal and transmural (Intramural fibroids originate in the central myometrium but don't extend to the endometrium or serosa; transmural fibroids extend through the entire uterine wall, from the endometrial lining to serosa) [10], and the uterine location into anteverted, midposition and retroverted [11].…”
Section: Patientsmentioning
confidence: 99%
“…Another study at China comparing HIFU, myomectomy and hysterectomy for treating symptomatic uterine fibroids showed that HIFU caused substantially less morbidity than surgery, with similar longterm QoL [20]. HIFU treatment seems to show equal quality in ablating uterine fibroids in patients with an anteverted uterus and the more difficult to treat retroverted uterus [21].…”
Section: Discussionmentioning
confidence: 99%